Sintomas vocais, autopercepção da voz e condições ambientais de trabalho de teleoperadores - Nathália Franco Cunha Caldeira (2018)
Objectives: to estimate the frequency of vocal symptoms and to describe self-perception of voice and self-reported environmental work conditions by telemarketers; to verify the association between vocal symptoms and sociodemographic variables (gender, age, schooling, length of service and average number of calls received on the workday), self-perception of self-reported voice and work environment by telemarketers. Method: an analytical cross-sectional study with 80 teleoperators from a teleservice company, from a Brazilian city, who agreed to participate in the study, approved by the Research Ethics Committee, according to ETIC # 1,729,975. The instrument used for research was a questionnaire prepared by researchers, divided into four parts. The first part inferred the sociodemographic data referring to gender, age, length of service, schooling, if studied at the time of the research and the average number of calls received per working day. The second part consisted of questions regarding self-perception of vocal quality (very good / good, regular / poor), speech speed (context-appropriate, fast or too slow), diction (understanding of the message said: adequate or not adequate) , volume (adequate, weak or too strong), tone of voice (suitable, voice too thick or too thin). There was also a question about tired and hoarse voice self-perception at the end of the day. The third part explored self-perception of the work environment with information on ventilation (satisfactory or unsatisfactory), temperature (satisfactory or unsatisfactory), noise (satisfactory or unsatisfactory), sound competition / need to raise voice (yes or no) and air pollution (satisfactory or unsatisfactory). In the fourth part was inserted the Questionnaire of Signs and Symptoms - (QSSV) elaborated in English translated and adapted to Portuguese, which is composed of 14 items and aims to determine the occurrence of vocal signs and symptoms in relation to voice use at work. We performed a descriptive analysis of the data with measures of central tendency dispersion. Subsequently, the nonparametric test for the independent samples, Mann-Whitney and the Spearman correlation test were used to compare the groups. The level of significance of 5% was considered. Results: most participants (86%) report presence of some vocal symptom and more than half of them (56%) have complaints ranging from 3 to 5 symptoms, the most common being dry throat (n=49) and pain of throat (n=29). As for self-perception of the voice, most authors reported vocal quality as very good or good (85%), believe that voice tone (77.5%), volume (72.5%) and speech speed (56.3%), and reported self-perception of a tired and hoarse voice at the end of the day (65%). Regarding the work environment, most telemarketers reported that it is necessary to raise the voice to speak on the telephone because of the sound competition and most classified the aspects of ventilation (73.8%), temperature (71.2%), noise (86.2%) and air pollution (57.5%) as unsatisfactory. There was no association between the number of vocal symptoms and sociodemographic variables. There was an association between a higher mean of vocal symptoms with inadequate diction, voice volume and speech rate, with tired and hoarse voice reporting at the end of the day, in telemarketers with the highest number of calls per work day and who reported environmental aspects of work not satisfactory for ventilation and temperature (p0.005). Conclusion: Most telemarketers report presence of some vocal symptom, more than half of them have complaints ranging from 3 to 5 symptoms being the most present dry throat and sore throat. Regarding self-perception of voice, most telemarketers have self-perception of vocal quality, tone of voice, volume and speech speed within normality patterns, however, most do not consider diction itself satisfactory to the client's understanding and self-perceive quality. voice tired and hoarse at the end of the day. Regarding the environmental conditions of work, most telemarketers report that it is necessary to raise the voice to speak on the telephone because of the sound competition and most perceive an inadequacy of the work environment in relation to ventilation, temperature, noise and air pollution. There is an association between a higher mean number of vocal symptoms and teleoperators who have self-perception of speech, vocal volume, speech rate as not adequate, perception of a tired and hoarse voice at the end of the day, receiving more calls per day of work and also with ventilation and temperature, perceived as unsatisfactory in the workplace. The results show that the presence of vocal symptoms in teleoperados is multifactorial and alert to measures of prevention of vocal care for this population.